PENGARUH DISIPLIN KERJA MOTIVASI NON MATERIAL INSENTIVE DAN PENDIDIKAN PELATIHAN (DIKLAT) TERHADAP PRESTASI KERJA TENAGA MEDIS RUMAH SAKIT UMUM WANGAYA - Ni Nyoman Supiatni; AAA.Mirah Kencanawati (Politeknik Negeri Bali, 2013)
The purpose from this research is to recognize the effect of work discipline, incentive non material motivation and educational training in regard to medical advisor performance both simultaneous and partial and recognize dominant variable which influence the performance. This research took place at Wangaya Public Hospital with address at Jalan Kartini Number 133 Denpasar – Bali with respondent amount 88 medical advisors. The data analyze technique that was used to verify hypothesis is factor analysis which has the purpose to recognize how far the variable that was studied can be explained by each dimension. Furthermore, used multifarioous linier regression analysis to recognize simultaneous effect and its partial and decide dominant variable which effected performance. Based on the analysis result was recognized that Work Discipline, Incentive Non Material Motivation, Educational and Training have the effect in a simultaneous in regard to medical advisor performance with contribution amounting to 82,9 percents where incentive non material motivation variable makes into the form of dominant factor in regard to medical advisor performance of Wangaya Public Hospital and the rest amounting to 17,1 percents were effected by the variable outside studied. Based on research result so the suggestion can be given to the Hospital Director and its row must be more to observe safety factor and medical advisor comfort, work placement, work time, appropriate educational and training assigment so that tey can increase medical advisor performance at Wangaya Public Hospital in Denpasar.